2022
DOI: 10.3390/su14073829
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Biochars Derived from the Pyrolysis and Co-Pyrolysis of Rubberwood Sawdust and Sewage Sludge for Further Applications

Abstract: This study investigated the characteristics of biochars derived from the pyrolysis of rubberwood sawdust (RWS) and sewage sludge (SS) and their co-pyrolysis at mixing ratios of 50:50 and 75:25. Biochars were produced at 550 °C through slow pyrolysis in a moving bed reactor and then characterized. Results showed that the rubberwood sawdust biochar (RWSB) had high carbon content (86.70 wt%) and low oxygen content (7.89 wt%). By contrast, the sewage sludge biochar (SSB) had high ash content (65.61 wt%) and low ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 101 publications
(146 reference statements)
1
15
0
1
Order By: Relevance
“…According to Deng et al K, Ca, Mg, Na, Si, Fe and Al are the dominant elements in sewage sludge biochars (SSB) from pyrolysis or co-pyrolysis [ 130 ]. Previous studies have shown that inorganic elements are often retained in SSB after pyrolysis because they do not decompose or volatilize at pyrolysis temperatures of 400–600 °C [ 58 ]. The P content of plants ranges from 0.1% to 1.0%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Deng et al K, Ca, Mg, Na, Si, Fe and Al are the dominant elements in sewage sludge biochars (SSB) from pyrolysis or co-pyrolysis [ 130 ]. Previous studies have shown that inorganic elements are often retained in SSB after pyrolysis because they do not decompose or volatilize at pyrolysis temperatures of 400–600 °C [ 58 ]. The P content of plants ranges from 0.1% to 1.0%.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the pyrolysis temperature of woody sapwood produces a biochar with a greater number of pores. It is caused by the thermal decomposition of lignocellulosic components [ 58 ]. Most biochars used for soil amendment are alkaline, however, biochar pH values between 3.1 and 12.0 have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Feedstock type and pyrolysis temperature influence the quantity of ash in biochar and in turn the use to which the biochar can be put (Ali et al, 2022a). Generally, biochar from sewage sludge and faecal sludge have higher ash contents than biochar from wood and agricultural/food processing residue.…”
Section: Feedstock Typementioning
confidence: 99%
“…Te important physical characteristics of biochar which is able to tune its potential for specifc use include production yield, surface morphology, bulk density, and fxed carbon [4]. Moreover, its chemical properties, such as pH, electrical conductivity (EC), elemental analyses, cation exchange capacity (CEC), and calcium carbonate contents are also the most important features of the biochar which are mainly determined by the feedstock type and the pyrolysis temperature applied [5].…”
Section: Introductionmentioning
confidence: 99%